Relationship between Serum Resistin and Insulin Resistance among Obese Non-Diabetic Patients in a Nigerian Tertiary Hospital (Nigerian Journal of Physiological Sciences, 2025)
There is paucity of information on the relationship between resistin and cardiometabolic outcome among non-diabetic obese in Africa, especially Nigeria with a growing prevalence of obesity and cardiovascular events. This study aims to elucidate the relationship between serum resistin and insulin resistance among non-diabetic obese patients. This is a cross-sectional study, involving 100 non-diabetic obese and 100 non-obese Nigerians. Participants waist circumference, abdominal circumference and waist-hip ratio were measured alongside fasting blood glucose (FBG), lipid profile, remnant cholesterol and blood pressure. Serum resistin and insulin were determined with ELISA technique. Insulin resistance was assessed using the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) formula. Data was analyzed with Manny-Whitney test to compares the median of the observation between the two groups and chi-square for association test.  Although FBG, serum insulin level and HOMA-insulin resistance (p